Using methods for solving trigonometric equations in a school mathematics course (Journal of Educational Sciences, 2023)
The article describes the program of the trigonometry section in the school mathematics course andthe application of trigonometry in life. The introduction defines trigonometric equations and mentionsthe types of solutions to the equation. The examples show methods for solving trigonometric equations.The ways of solving simple trigonometric equations and the possibilities of their independent solutionare illustrated. Separately, methods for solving equations were noted, which are actually little used inthe school mathematics course. According to the results of the study, about ten types of methods forsolving trigonometric equations were identified. In order to reveal the essence of the methods of solvingtrigonometric equations, the problems for each method are considered and the ways of deducingthese problems are shown. In addition, this article discussed the difficulties faced by students in solvingtrigonometric equations, and the methods proposed by A. G. Mordkovich in solving these problems.In the final part, the results of the methodological experience of teachers are summarized, whenstudents practiced solving a series of problems on the topic “Methods for solving trigonometric equations”and teachers identified abilities that can be developed in students to solve the equation. In thefuture, it is planned to publish a specific methodological manual on the topic “Trigonometric equationsand inequalities”.Key words: trigonometric equation, methodology, equation solution, methods.